2010
DOI: 10.1073/pnas.1007745107
|View full text |Cite
|
Sign up to set email alerts
|

Competition–defense tradeoffs and the maintenance of plant diversity

Abstract: Ecologists have long observed that consumers can maintain species diversity in communities of their prey. Many theories of how consumers mediate diversity invoke a tradeoff between species' competitive ability and their ability to withstand predation. Under this constraint, the best competitors are also most susceptible to consumers, preventing them from excluding other species. However, empirical evidence for competition-defense tradeoffs is limited and, as such, the mechanisms by which consumers regulate div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
118
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(124 citation statements)
references
References 26 publications
5
118
1
Order By: Relevance
“…Several studies indicated that there is often no interspecific trade‐off between defense and competitiveness as a higher resource supply adversely affected defended plants (Lind et al., 2013; Viola et al., 2010). In fact, Lind et al.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies indicated that there is often no interspecific trade‐off between defense and competitiveness as a higher resource supply adversely affected defended plants (Lind et al., 2013; Viola et al., 2010). In fact, Lind et al.…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies have experimentally manipulated abiotic or biotic limiting factors (e.g., through nitrogen addition or herbivore exclusion) to identify filters driving the assembly and composition of plant communities and to search for trade-offs between plant strategies (Viola et al 2010, Lind et al 2013), only few have provided insight into the underlying ecological mechanisms (HilleRisLambers et al 2012). Scha¨dler et al (2003) related the response of 13 herbaceous plant species to invertebrate herbivore exclusion with plant palatability based on herbivore performance of a generalist slug and the generalist house cricket, but found no relationship between the palatability of plants and their cover change due to herbivore exclusion.…”
Section: Figmentioning
confidence: 99%
“…However, also generalist herbivores can have stabilizing effects on plant communities when they switch host or food plant species and consume disproportionally whichever species is most abundant (Murdoch 1969, Chase et al 2002. Other theories on how herbivores can promote coexistence require a trade-off between the vigorous growth of plants and their defense against consumers, assuming that defense is costly and constrains investment in other important traits (Coley et al 1985, Herms and Mattson 1992, Viola et al 2010, Kempel et al 2011, Lind et al 2013. If the plants growing most vigorously in a community are also the least defended ones, herbivores promote coexistence by selectively feeding on more vigorously growing and hence less defended plant species (Pacala andCrawley 1992, Carson andRoot 1999), thereby reducing average fitness differences between species, which is considered as an equalizing mechanism (Chesson 2000).…”
Section: Introductionmentioning
confidence: 99%
“…These zero values are potentially important features of the data, so we added the minimum non-zero value for that variable to every observation before calculating the log response ratio. This method of adjustment has been used as a conservative estimate of the log response ratio in data where species were not detected in some samples (Viola et al 2010). We also computed log response ratios for the richness, biomass, and number captured for the four most commonly sampled taxa: three-spined stickleback (Gasterosteus aculeatus), pumpkinseed sunfish (Lepomis gibbosus), prickly sculpin (Cottus asper), and juvenile minnows (Cyprinidae).…”
Section: Discussionmentioning
confidence: 99%